Corpus Linguistics and Cinematic Discourse: Lexical Bundles in Mainstream Film Scripts - Xu, Runze; Wijitsopon, Raksangob (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Hollywood blockbuster films have long attracted not only mass audiences but also scholarly attention. In line with contemporary applied linguistics interests in telecinematic discourse, the present study draws upon concepts and techniques in corpus linguistics to describe the language of American mainstream film scripts. The concept of lexical bundles was employed to identify linguistic patterns characteristic of scripts of American mainstream films produced by entertainment conglomerates, which are popular in the U.S. Results show that American mainstream film scripts are characterized mainly by spoken formulaic expressions. However, descriptive expressions, such as place-referential and action-related lexical bundles, also predominantly make up the given register. Further qualitative analysis reveals that these common multi-word expressions have functional contributions to film scripts in terms of creation of conflicts in plots, characterization, and building engagement with audiences.